2013
DOI: 10.2174/0929866511320060010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Expression and Characterization of the Porcine β Defensin 2 in E. coli

Abstract: Porcine β defensin 2(pBD2)is a cationic 37-amino acid antimicrobial peptide with disulfide bonds. Synthetic pBD2 had broad antimicrobial activity against pathogenic bacteria, and thus pBD2 could be a good candidate as a bactericidal agent for pigs. This study reported the successful recombinant expression of pBD2 in Escherichia coli and analysis of its antimicrobial activity, its hemolytic activity, salt-tolerance and thermal stability as well. The pBD2 gene, obtained by RT-PCR using the tongue total RNA as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 0 publications
6
28
0
Order By: Relevance
“…pBD2 is highly expressed in the kidney, liver, and tongue (Chen et al, 2010). Moreover, pBD2 shows high antimicrobial activity against bacteria, including multi-resistant bacteria, which makes it a good candidate for antibiotics (Zhang et al, 2000;Veldhuizen et al, 2008;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…pBD2 is highly expressed in the kidney, liver, and tongue (Chen et al, 2010). Moreover, pBD2 shows high antimicrobial activity against bacteria, including multi-resistant bacteria, which makes it a good candidate for antibiotics (Zhang et al, 2000;Veldhuizen et al, 2008;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed pBD2 to have high antimicrobial activity against bacteria, including multidrug-resistant bacteria isolated from sick fowl (Veldhuizen et al, 2008;Li et al, 2013a), which makes it good candidate for antibiotic development. Furthermore, pBD2 showed low hemolytic activity, high salt-tolerance, and strong thermal stability, which are important properties for its practical application (Li et al, 2013a). However, the anti-bacterial mechanism of pBD2 and its role in the immune system are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…His-pBD2 was expressed by inducing the Escherichia coli strain BL21(DE3)-pET-pBD2, which was constructed in our laboratory, with isopropyl β-D-1-thiogalactopyranoside (IPTG), and the protein was purified as previously described (Li et al, 2013a;Gao et al, 2015). The purified his-pBD2 was analyzed by SDS-PAGE, and used for the preparation of antibodies.…”
Section: Expression and Purification Of His-pbd2mentioning
confidence: 99%
See 2 more Smart Citations